1993
DOI: 10.2307/1131270
|View full text |Cite
|
Sign up to set email alerts
|

Disorganized Infant Attachment Classification and Maternal Psychosocial Problems as Predictors of Hostile-Aggressive Behavior in the Preschool Classroom

Abstract: This study of 62 low-income families examined the relation between maternal and infant measures assessed at 18 months infant age and child behavior problems at age 5 as rated by preschool teachers. The infancy assessments included measures of mother-infant interaction, maternal psychosocial problems, infant cognitive development, and infant attachment security, including the disorganized/disoriented classification. The strongest single predictor of deviant levels of hostile behavior toward peers in the classro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
187
3
20

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 418 publications
(226 citation statements)
references
References 24 publications
16
187
3
20
Order By: Relevance
“…They found that the quality of the attachment relationship assessed at 12 and 18 months of age with the Strange Situation is predictive of the ability to deal with the classical delay of gratification task at 6 years of age, with an average waiting time higher for children with a secure attachment compared to children with insecure attachment. This result confirms the evidence, already present in the literature, about the difficulty in self-regulation and in the control of impulsivity for the insecure attached children (see for example, Lyons-Ruth et al, 1993; Shaw and Vondra, 1995). …”
Section: Introductionsupporting
confidence: 90%
“…They found that the quality of the attachment relationship assessed at 12 and 18 months of age with the Strange Situation is predictive of the ability to deal with the classical delay of gratification task at 6 years of age, with an average waiting time higher for children with a secure attachment compared to children with insecure attachment. This result confirms the evidence, already present in the literature, about the difficulty in self-regulation and in the control of impulsivity for the insecure attached children (see for example, Lyons-Ruth et al, 1993; Shaw and Vondra, 1995). …”
Section: Introductionsupporting
confidence: 90%
“…Psychosocial risk factors, such as low family SES and maternal psycopathology, and socio-demographic risk factors, such as very young maternal age and single parenting, are among the most theoretically relevant and empirically investigated risk conditions. Although results of this line of research are substantially coherent in identifying the detrimental effect of each factor, they also point out to a complex cumulative model of risk according to which a single factor may not be influential itself whereas its predictive value might be moderated by the association with other risk conditions or by its degree of intensity (Belsky, 1984; Greenberg et al, 1993; Lyons-Ruth et al, 1993; Hubbs-Tait et al, 1996). Several intervention programs have been developed for at-risk families and some have shown positive effect on mother–child relationship quality (Bakermans-Kranenburg et al, 2003) reducing the impact of risk factors on mother and child psychological health (Kohlhoff and Barnett, 2013).…”
Section: Discussionmentioning
confidence: 87%
“…However, the parent–child relationship can be affected by several psychosocial and socio-demographic risk factors that undermine its quality and in turn play a negative role in short and long term child psychological wellbeing (Sameroff, 1998, 2000; Choe et al, 2013). Classical research on the psychological development of children living in at risk families supports additive models according to which psychological problems are not the result of one specific risk factor but may be instead predicted by the combined presence of different factors (Greenberg et al, 1993; Lyons-Ruth et al, 1993; Hubbs-Tait et al, 1996). Also, established models of parenting (Belsky, 1984) postulate that the quality of the parent–child relationship is the integrated result of three sets of factors: parent characteristics, infant characteristics, and context which can influence parenting in a supportive or stressful way.…”
Section: Introductionmentioning
confidence: 99%
“…Van Ijzendoorn et al [16] found in their meta-analysis that while 20.4% of their sample (n = 6,281) showed disorganized attachment, this figure increased to 48% in maltreated children (n = 165). Other studies found values of up to 82% in samples of maltreated children [45,46]. While secure attachment can be seen as a protective factor for the development of externalizing behavior [15], disorganized attachment can be regarded as a vulnerability for personality disorders and other psychopathologies [47] and is associated with increased externalizing behavior [16].…”
Section: Attachment and Mentalizationmentioning
confidence: 99%